Oden Arctic Technology Research Cruise 2013 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during 19 August to 25 September 2013 - Oden Arctic Technology Research Cruise 2013 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during 19 Augusti to 25 September 2013 - Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2017)
In late summer 2013, the research expedition Oden Arctic Technology Research Cruise (OATRC 2013) took place in the waters northeast of Greenland onboard the Swedish icebreaker Oden.

The expedition was carried out by the Norwegian University of Science and Technology (NTNU) in collaboration with the Swedish Polar Research Secretariat. OATRC 2013 was a project associated with Sustainable Arctic Marine and Coastal Technology (SAMCoT), which is a centre for research-based innovation, initiated by the Research Council of Norway and hosted by NTNU. OATRC 2013 was a follow-up to last year’s expedition to this region.

Purpose:

The main scientific scope of the research expedition was:
Collection of data necessary to build, calibrate and validate models for:
floaters in ice, ice management operations, iceberg/sea ice drift, ice/met/ocean statistics, evaluation of new technologies and environmental research.

This data set contains meteorological, oceanographic and ship data collected during the expedition Oden Arctic Technology Research Cruise 2013 (OATRC 2013), which was an international research cruise using the icebreaker Oden in the Arctic Ocean. The expedition embarked from Svalbard, Norway on 19 Augusti and proceeded along the coast of Greenland from where the expedition returned to Svalbard on September 23, 2013.

Data include:

Meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Photosynthetic Active Radiation (PAR).

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.

I slutet av sommaren 2013 gick forskningsexpeditionen Oden Arctic Technology Research Cruise (OATRC 2013) till vattnen nordost om Grönland med den svenska isbrytaren Oden.
Expeditionen var ett samarbete mellan Norges teknisk-naturvitenskapelige universitet i Trondheim (NTNU) och Polarforskningssekretariatet. OATRC 2013 var ett projekt inom SAMCoT (Sustainable Arctic Marine and Coastal Technology), som är ett center för forskningsbaserad innovation som inrättats av Norges forskningsråd med NTNU som värd. Expeditionen var en uppföljning av en expedition i samma område 2012.

Syfte:

Syftet med expeditionen var att ombord på Oden bland annat studera havsisens och isbergens fysikaliska och mekaniska egenskaper, isbrytaren Odens prestanda och framkomlighet under skiftande isförhållanden samt egenskaper hos drivande havsis och isberg under varierande meteorologiska och oceanografiska förhållanden. Under expeditionen testades och utvärderades även ny teknologi.

This data set contains meteorological, oceanographic and ship data collected during the expedition Oden Arctic Technology Research Cruise 2013 (OATRC 2013), which was an international research cruise using the icebreaker Oden in the Arctic Ocean. The expedition embarked from Svalbard, Norway on 19 Augusti and proceeded along the coast of Greenland from where the expedition returned to Svalbard on September 23, 2013.

Data include:

Meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Photosynthetic Active Radiation (PAR).

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.
Oden Arctic Technology Research Cruise 2013 - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden från 19 augusti till 25 september 2013 - Oden Arctic Technology Research Cruise 2013 - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden under 19 augusti till 25 september 2013
Keywords: Meteorology; Meteorologi; ATMOSPHERE; ATMOSPHERIC WINDS; SURFACE WINDS; ATMOSPHERIC TEMPERATURE; AIR TEMPERATURE; ATMOSPHERIC WATER VAPOR; HUMIDITY; ATMOSPHERIC PRESSURE; SURFACE PRESSURE; OCEANS; SALINITY; CONDUCTIVITY; OCEAN TEMPERATURE; WATER DEPTH; SEAFLOOR TOPOGRAPHY; BATHYMETRY; BIOSPHERE; VEGETATION; PHOTOSYNTHETICALLY ACTIVE RADIATION; The icebreaker Oden; Isbrytaren Oden; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Engineering and Technology; Teknik; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Environment; Miljö